2009
DOI: 10.1007/s12665-009-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial functional diversity as influenced by cadmium, phenanthrene and degrade bacteria application

Abstract: There are increasing concerns over compound pollution in northeast of China and its bioremediation. Cd, Phe, degradation bacteria W.J and their combination on soil microbial community function were assessed with the BIOLOG method. The microbial community was extracted from the soil with different treatments. Average color development, richness, Shannon-Weaver index, and principal component analysis on OD standardized data were performed. The results showed that soil microbial metabolic diversity in CK was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In our study, the POD activity was not affected by naphthalene treatment, which may be due to the formation of peroxidase in the biochemical oxidation reaction of biological respiration and organic matter. Several studies 6,30,31 have shown that naphthalene treatment did not significantly alter the soil respiration rate; thus, naphthalene treatment did not have an impact on peroxidase activity. Polyphenol oxidase activity is usually related to microbial community structure 2 .…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the POD activity was not affected by naphthalene treatment, which may be due to the formation of peroxidase in the biochemical oxidation reaction of biological respiration and organic matter. Several studies 6,30,31 have shown that naphthalene treatment did not significantly alter the soil respiration rate; thus, naphthalene treatment did not have an impact on peroxidase activity. Polyphenol oxidase activity is usually related to microbial community structure 2 .…”
Section: Discussionmentioning
confidence: 94%
“…For the CLPP analysis, the carbon sources shown to be more informative regarding the effects of heavy metals on bacterial communities were selected. Other sources (such as D-xylose and D-cellobiose) identified in previous studies were also considered [50] [52] . Canonical discriminant analysis (CDA) was performed on the selected carbon sources (β-Methyl-D-Glucoside, i-Erythritol, D-Mannitol, α-Cyclodextrin, N-Acetyl-D-Glucosamine, α-D-Lactose, and the two previously mentioned).…”
Section: Methodsmentioning
confidence: 99%